Near-infrared spectroscopy (NIRS) neurofeedback as a treatment for children with attention deficit hyperactivity disorder (ADHD)—a pilot study - Marx, Anna-Maria; Ehlis, Ann-Christine; Furdea, Adrian; Holtmann, Martin; Banaschewski, Tobias; Brandeis, Daniel; Rothenberger, Aribert; Gevensleben, Holger; Freitag, Christine M.; Fuchsenberger, Yvonne; Fallgatter, Andreas J.; Strehl, Ute (Frontiers in Human Neuroscience, 2015)
In this pilot study near-infrared spectroscopy (NIRS) neurofeedback was investigated as a new method for the treatment of ADHD. Oxygenated hemoglobin in the prefrontal cortex of children with ADHD was measured and fed back. 12 sessions of NIRS-neurofeedback were compared to the intermediate outcome after 12 sessions of EEG-neurofeedback (slow cortical potentials, SCP) and 12 sessions of EMG-feedback (muscular activity of left and right musculus supraspinatus). The task was either to increase or decrease hemodynamic activity in the prefrontal cortex (NIRS), to produce positive or negative shifts of SCP (EEG) or to increase or decrease muscular activity (EMG). In each group nine children with ADHD, aged 7 to 10 years, took part. Changes in parents’ ratings of ADHD symptoms were assessed before and after the 12 sessions and compared within and between groups. For the NIRS-group additional teachers’ ratings of ADHD symptoms, parents’ and teachers’ ratings of associated behavioral symptoms, childrens’ self reports on quality of life and a computer based attention task were conducted before, 4 weeks and 6 months after training. As primary outcome, ADHD symptoms decreased significantly 4 weeks and 6 months after the NIRS training, according to parents’ ratings. In teachers’ ratings of ADHD symptoms there was a significant reduction 4 weeks after the training. The performance in the computer based attention test improved significantly. Within-group comparisons after 12 sessions of NIRS-, EEG- and EMG-training revealed a significant reduction in ADHD symptoms in the NIRS-group and a trend for EEG- and EMG-groups. No significant differences for symptom reduction were found between the groups. Despite the limitations of small groups and the comparison of a completed with two uncompleted interventions, the results of this pilot study are promising. NIRS-neurofeedback could be a time-effective treatment for ADHD and an interesting new option to consider in the treatment of ADHD.